Morphological phylogeny of Megachilini and the evolution of leaf-cutter behavior in bees (Hymenoptera: Megachilidae): Evolution of leaf-cutter behavior in bees - Gonzalez, Victor H.; Gustafson, Grey T; Engel, Michael S (Journal of Melittology, 2019)
A unique feature among bees is the ability of some species of Megachile Latreille s.l. to cut and process fresh leaves for nest construction. The presence of a razor between the female mandibular teeth (interdental laminae) to facilitate leaf-cutting (LC) is a morphological novelty that might have triggered a subsequent diversification in this group. However, we have a limited understanding of the phylogeny of this group despite the large number of described species and the origins and patterns of variations of this mandibular structure are unknown. Herein, using a cladistic analysis of adult external morphological characters, we explored the relationships of all genera of Megachilini and the more than 50 subgenera of Megachile s.l. We coded 272 characters for 8 outgroups and 114 ingroup species. Depending on the weighting scheme (equal or implied weighting), our parsimony analyses suggested the monophyly of Megachile s.l. and that either Noteriades Cockerell or the clade Coelioxys Latreille + Radoszkowskiana Popov is the extant sister group of all other Megachilini. In addition, we conducted Bayesian total-evidence tip-dating analyses to examine other possible hypotheses of relationships and patterns of variation of the interdental lamina. Our analyses suggest that interdental laminae developed asynchronicaly from two different structures in the mandible, and differ in their phenotypic plasticity. Character correlation tests using phylogenetic pairwise comparisons indicated that the presence of interdental lamina is not associated with head size, mandible size and shape, and pubescence on the adductor interspace. We discuss the implications of our findings for the classification of Megachilini and the development of novel evolutionary, ecological, and functional hypotheses on this behavior. New taxa established are Pseudoheriadini Gonzalez & Engel, new tribe, Ochreriadini Gonzalez & Engel, new tribe, Cremnomegachile Gonzalez & Engel, new genus, Rozenapis Gonzalez & Engel, new genus, and Saucrochile Gonzalez & Engel, new genus, along with the following new combinations: Cremnomegachile dolichosoma (Benoist), new combination, Rozenapis ignita (Smith), new combination, and Saucrochile heriadiformis (Smith), new combination.